Cardiac Cell and Gene Transfer - Metzger, Joseph M.; Metzger, Joseph M. (Methods in Molecular Biology, 2003)
Cellular and gene-based experimental techniques promise powerful new therapeutic agents for the remediation of both acquired and inherited cardiovascular disease. In Cardiac Cell and Gene Transfer: Principles, Protocols, and Applications, Joseph M. Metzger and a panel of leading scientific experts detail many novel techniques and strategies for the cellular and genetic modification of heart function. These highly experienced authors provide step-by-step protocols for vector production and purification, for gene and cell delivery techniques, and for physiological assessment in vivo and in vitro. Timely, authoritative, and state-of-the-art, Cardiac Cell and Gene Transfer: Principles, Protocols, and Applications constitutes an invaluable guide to all the new cellular and gene-based technologies needed by basic and clinical investigators working to illuminate today's unanswered questions about heart disease and ultimately to improve the heart performance in all their patients.